Pharmacoeconomic analysis of the application of follitropin alfa in combination with assisted reproductive technologies - K. A. Perova; D. G. Shchurov; D. V. Blinov; N. V. Bashmakova; N. Z. Musina (Фармакоэкономика)
Objective: to evaluate clinical-economic feasibility and impact of follitropin alfa on the state healthcare budget of the Russian Federation in the population of women with diagnosed infertility and poor ovarian response, who undergo treatment with assisted reproductive technologies (ART).Material and methods. A cost minimization analysis to evaluate clinical-economic feasibility of follitropin alfa in women with infertility and poor ovarian response who underwent ART was performed. The model of the budget impact analysis included the costs required for the ovarian stimulation of patients distributed by various variants of their management. The current practice involved the application only of fixed dose combinations (FDC) of follitropin alfa + lutropin alfa. The expected practice suggested a change in the approach by shifting 25% of patients with poor ovarian response from FDC of follitropin alfa + lutropin alfa to follitropin alfa. A time horizon of modeling was 1 year.Results. The cost minimization analysis demonstrated that the application of drug with international nonproprietary name follitropin alfa is characterized by the cost cut of 12,020 rubles (–21.56%) per patient compared with FDС of follitropin alpha + lutropin alpha. The results of budget impact analysis showed that a shift of 25% of population from FDC of follitropin alfa + lutropin alfa to follitropin alfa could cut direct medical costs by 7.96 million rubles per year (–5.39%).Conclusion. Evaluation of clinical-economic feasibility and budget impact analysis showed that the application of follitropin alfa during ovarian stimulation in women with infertility and poor ovarian response leads to a decrease in budget expenses.